Huisgen-based conjugation of water-soluble porphyrins to deprotected sugars: Towards mild strategies for the labelling of glycans - SCANLAN, EOIN (My University, 2014)
Fully deprotected alkynyl-functionalised mono- and oligosaccharides undergo CuAAC-based conjugation with water-soluble porphyrin azides in aqueous environments. The mild reaction conditions are fully compatible with the presence of labile glycosidic bonds. This approach provides an ideal strategy to conjugate tetrapyrroles to complex carbohydrates
PUBLISHED
Keywords: Chemistry